Exchange Rate Volatility Under Peg : Do Trade Patterns Matter? - Lonkeng Ngouana, Constant (IMF Working Papers; Working Paper, 2012)
This paper assesses the role of trade patterns in shaping the volatility of the effective exchange rate under two alternative peg regimes: a hard peg to a single currency and a peg to a basket of currencies. I link the changes in the nominal effective exchange rate of a pegged currency to the fluctuations of its anchor vis-a-vis other major currencies, with an emphasis on the dynamics of trade patterns. In an application to the WAEMU (West African Economic and Monetary Union), I find that the nominal effective exchange rate of the union was twice as volatile under the hard peg to the euro as it would have been under a hypothetical basket peg over the past decade. This result was driven by the substantial shifts that occurred in WAEMU trade patterns, away from euro area countries and toward the ?"BICs" (Brazil, India, and China). These findings suggest that policymakers should pay as much attention to the type of peg as to pegging in itself, with a particular focus on the dynamics of trade patterns.